각막 교차결합술을 시행받은 원추각막 환자에서 각막전면높이 변화에 따른 결과 분석 - 양지호; Ji Ho Yang; 진경현; Kyung Hyun Jin (Daihan angwa haghoi jabji, 2013)
목적: 원추각막환자에서 각막교차결합술 후 각막전면높이변화에 따른 결과를 분석하고자 한다. 대상과 방법: 진행성 원추각막환자 15안을 대상으로 각막교차결합술을 시행하였다. 술 후 각막형태변화에 따른 최대교정시력, 굴절력 및 각막형태변화등을 분석하였다. 결과: 술 후 12개월 각막전면높이변화에 따라 각막중심부가 편평해지는 그룹 1과 가팔라지는 그룹 2로 나누었다. 술 전 각막중심점과 각막첨부사이의 거리는 그룹 1 (0.19 ± 0.13 mm)에서 그룹 2 (0.47 ± 0.23 mm)보다 짧았다(p=0.021). 12개월에 최대교정시력 (logMAR)은 그룹 1에서 0.68 ± 0.78에서 0.57 ± 0.81로 호전되었고(p=0.115) 그룹 2에서 0.51 ± 0.34에서 0.56 ± 0.38로 감소되었다(p=0.109). 최대각막곡률치는 그룹 1에서 63.01 ± 19.07D에서 58.95 ± 16.32D로 감소되었고(p=0.017) 그룹 2에서는 60.70 ± 9.46D에서 61.29 ± 7.51D로 증가되었다(p=0.674). 결론: 각막중심부가 편평해지는 그룹이 가팔라지는 그룹보다 임상 및 광학적 결과에서 호전되는 양상을 관찰할 수 있었다. 각막전면높이변화 및 술 전 각막중심점과 첨부사이의 거리는 각막 교차결합술의 결과에 영향을 미치는 인자로 고려해 볼 수 있다. <대한안과학회지 2013;54(2):199-209> Purpose: To report the results according to anterior elevation changes following corneal crosslinking (CXL) treatment for keratoconus. Methods: The present retrospective study included 14 patients (15 eyes) with progressive keratoconus who underwent CXL with a follow-up of 12 months. Patients were classified into 2 groups according to pre and postoperative anterior elevation difference maps. On the preoperative anterior elevation map, distances from maximum anterior elevation to pupil center were compared between the 2 groups. The outcome of best correct visual acuity (BCVA), maximum keratometry and parameters of corneal topography were compared between the 2 groups before CXL as well as 6 and 12 months after CXL. Results: The anterior elevation changes were classified as group 1 (-7.88 ± 10.53 μm) or group 2 (8.71 ± 5.99 μm) (p = 0.001). The preoperative corneal topography of eyes observed in group 1 (0.19 ± 0.13 mm) had shorter mean distances from maximum anterior elevation to pupil center than eyes in group 2 (0.47 ± 0.23 mm) (p = 0.018). BCVA (log MAR) improved from 0.68 ± 0.78 to 0.57 ± 0.81 (p = 0.115) 12 months after CXL in group 1 and decreased from 0.51 ± 0.34 to 0.56 ± 0.38 (p = 0.109) 12 months after CXL in group 2. The maximum keratometry decreased from 63.01 ± 19.07D to 58.95 ± 16.32D (p = 0.017) in group 1 and increased from 60.70 ± 9.46D to 61.29 ± 7.51D (p = 0.674) in group 2. Conclusions: Clinical and optical effects improved postoperatively in group 1, and were stabilized in group 2. The preoperative distance from maximum anterior elevation to pupil center and the anterior elevation changes after CXL were factors in predicting the CXL outcome. J Korean Ophthalmol Soc 2013;54(2):199-209